Provision of Physically Disabled-Friendly Public Facilities at Recreation Park with a Case Study - Izza Shafini binti Zainal Abidin; Nurul Izza binti Mahadan; Mohd Zulkafli bin Mohamed (UNIVERSITAS SERAMBI MEKKAH, 2024)
The design of accessible public facilities for persons with disabilities (PWD) is crucial, especially in recreational park areas. This aligns with sustainable urban and community planning goals, which aim to provide well-being for all individuals without prejudice. The provision of PWD-friendly public facilities in recreational parks is often overlooked. This study aims to identify PWD's perceptions regarding the effectiveness of the design of PWD-friendly recreational parks. The research methodology adopts a quantitative approach, involving 47 respondents. The findings indicate that the state of public facilities in the study area requires significant improvement and renovation to enhance comfort for users with disabilities. Recommendations for providing accessible facilities for PWD in the study area aim to improve accessibility and user comfort while upholding their social rights